Upper tibial MRI vascular marks lost in early knee osteoarthritis - Michael Beverly (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background We describe upper tibial radiating vascular marks on MRI scans. They are lost in early osteoarthritis (OA). Methods A literature search revealed no previous description of upper tibial MRI radial vascular marks. Fifty-six consecutive patients with anteroposterior knee X-rays and an axial PD_SPAIR MRI scan of the same knee within 1 year were studied. Their mean age was 53.1 years (range 22–85) with 27 males and 29 females. The medial and lateral compartments of each knee were scored for osteoarthritis using the Kellgren-Lawrence (K-L) classification. Marks on the MRI scans were counted by layer and quadrant position. Results Radial vascular marks were present in the first axial upper tibial subchondral slice, peaked between 6 and 10 mm depth and were absent by 16 mm depth. There was no association with age, left or right knee, BMI, or weight. There was more K-L graded OA medially and more vascular marks laterally. There was an inverse correlation between the number of marks and early grades of osteoarthritis medially (p < 0.001) and laterally (p < 0.002). Conclusion We demonstrate previously undescribed subchondral vascular marks on axial MRI scans of the tibia and their inverse correlation with the presence and severity of early knee osteoarthritis. Our work offers a new insight into the possible vascular aetiology of osteoarthritis and potentially a means of earlier diagnosis and a therapeutic target.